Ischemic Brain Stroke and Mesenchymal Stem Cells: An Overview of Molecular Mechanisms and Therapeutic Potential - Yang Jingli; Wang Jing; Yasmeen Saeed (Hindawi Limited, 2022)
Ischemic brain injury is associated with a high rate of mortality and disability with no effective therapeutic strategy. Recently, a growing number of studies are focusing on mesenchymal stem cell-based therapies for neurodegenerative disorders. However, despite having the promising outcome of preclinical studies, the clinical application of stem cell therapy remained elusive due to little or no progress in clinical trials. The objective of this study was to provide a generalized critique for the role of mesenchymal stem cell therapy in ischemic stroke injury, its underlying mechanisms, and constraints on its preclinical and clinical applications. Thus, we attempted to present an overview of previously published reports to evaluate the progress and provide molecular basis of mesenchymal stem cells (MSCs) therapy and its application in preclinical and clinical settings, which could aid in designing an effective regenerative therapeutic strategy in the future.